Self-Efficacy Analysis as Mediating with Workload and Job Satisfaction Affects e-Performance - Setiadi, Iwan Kresna (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This study aims to analyze the role of self-efficacy as a mediator in the effect of workload and job satisfaction on electronic performance (E-Performance). The data analysis method uses a mediation model with self-efficacy variables as intermediaries, measured through the SmartPLS 4.0 application. The sample of this study amounted to 100 people taken from employees of companies engaged in the Logistics Industry. The results showed that workload did not have a significant effect on E-Performance, while job satisfaction had a positive and significant effect. Self-efficacy was found to mediate the relationship between workload and full E-Performance, as well as partially mediate between job satisfaction and E-Performance. The implications of these findings contribute to the understanding of the factors that influence electronic performance in the work environment, by highlighting the role of self-efficacy as a relevant mediator. These conclusions can help organizations in designing more effective management strategies to improve performance in the technological era.